2016
DOI: 10.1136/tobaccocontrol-2016-053119
|View full text |Cite
|
Sign up to set email alerts
|

When smokers quit: exposure to nicotine and carcinogens persists from thirdhand smoke pollution

Abstract: Homes of smokers remained polluted with THS for up to 6 months after cessation. Residents continued to be exposed to THS toxicants that accumulated in settled house dust and on surfaces before smoking cessation. Further research is needed to better understand the consequences of continued THS exposure after cessation and the efforts necessary to remove THS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
83
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 35 publications
(36 reference statements)
2
83
0
Order By: Relevance
“…Specifically, the GeoM of 86.4 ng/wipe was over three times higher than the levels of 25.6 ng/wipe in previous research on non-smoking adults living with active smokers. 4 In other research in which finger wipes of adults were analysed, we have reported GeoMs of 5.2 ng/wipe among non-smokers moving into an apartment formerly occupied by a smoker 5 and 630–650 ng/wipe among active smokers. 25 Because nicotine is specific to tobacco, its presence on children’s hands may serve as a proxy of tobacco smoke pollution in their immediate environment.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Specifically, the GeoM of 86.4 ng/wipe was over three times higher than the levels of 25.6 ng/wipe in previous research on non-smoking adults living with active smokers. 4 In other research in which finger wipes of adults were analysed, we have reported GeoMs of 5.2 ng/wipe among non-smokers moving into an apartment formerly occupied by a smoker 5 and 630–650 ng/wipe among active smokers. 25 Because nicotine is specific to tobacco, its presence on children’s hands may serve as a proxy of tobacco smoke pollution in their immediate environment.…”
Section: Discussionmentioning
confidence: 80%
“…Our ongoing research now includes hand surface area measurements so that we can compare new findings with our previous work. 16 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surface nicotine levels remained at the high BL levels for the first 2 weeks, before they started to decline over the following months, though they remained at or above levels found in homes of active smokers in California 20 22 25 28. Dust nicotine and TSNA concentrations remained at or near the very high BL levels for up to 3 months into the smoking ban before they declined to levels found in the homes of active smokers in California 25. One month after smoking resumed, all THS measures on the casino floor rebounded compared with levels observed during the ban.…”
Section: Discussionmentioning
confidence: 84%